Effect of Dasatinib on Oxidative Stress and Neovascularization in Experimental Corneal Neovascularization - Yildirim, Hakan; Balbaba, Mehmet; Canleblebici, Mehmet; Dal, Ali; Erdag, Murat; Ilhan, Nevin; Akdeniz Incili, Canan (Mary Ann Liebert, Inc, 2025)
Purpose: To compare the effects of topical bevacizumab and dasatinib on experimental corneal neovascularization and oxidative stress and to determine the effective dose of dasatinib. Methods: Forty-two healthy Wistar-Albino rats were randomly divided into six groups. The right corneas of all rats except group 1 were cauterized with silver nitrate. Group 2 received dimethyl sulfoxide, group 3 received topical bevacizumab (5 mg/mL, three times a day), and groups 4, 5, and 6 received dasatinib (2.5 mg/dL, 5 mg/dL, and 10 mg/dL, three times a day respectively), between days 1 and 7. The corneas were removed to determine the level of vascular endothelial growth factor (VEGF), platelet-derived growth factor (PDGF) values for neovascularization and superoxide dismutase (SOD), malondialdehyde (MDA), and protein carbonyl (PC) levels for analyzing oxidative stress. Nonparametric variance analysis and post hoc Tamhane test was used for statistical analysis. Results: The VEGF level was statistically significantly lower in groups 3, 4, and 5 compared with group 2 (P < 0.05). The PDGF, SOD and MDA levels were compared; there was significant difference between all the groups compared with group 2. However, the MDA level for group 6, compared with other treatment groups, had a higher value (P < 0.05). The PC levels compared were statistically significantly lower in groups 3 and 4 compared with group 2 (P < 0.05). Conclusions: Dasatinib 2.5 mg/dL was as effective as bevacizumab and seems to be dose-dependent and higher doses than 2.5 mg/dL show higher oxidative stress and an increase in neovascularization.
Keywords: corneal neovascularization; dasatinib; bevacizumab; oxidative stress